The AI spring of 2018. Issue 3 (June 2018) - Olhede, Sofia; Wolfe, Patrick
Abstract : As nations race for dominance in the field of artificial intelligence, Sofia Olhede andPatrick Wolfe consider the implications for statistics and statisticians Abstract : As nations race for dominance in the field of artificial intelligence, Sofia Olhede and Patrick Wolfe consider the implications for statistics and statisticians.